Simvastatin inhibits neural cell apoptosis and promotes locomotor recovery via activation of Wnt/β‐catenin signaling pathway after spinal cord injury. Issue 1 (23rd May 2016) - Gao, Kai; Shen, Zhaoliang; Yuan, Yajiang; Han, Donghe; Song, Changwei; Guo, Yue; Mei, Xifan
Abstract: Statins exhibit neuroprotective effects after spinal cord injury (SCI). However, the molecular mechanism underlying these effects remains unknown. This study demonstrates that the hydroxymethylglutaryl coenzyme A reductase inhibitor simvastatin (Simv) exhibits neuroprotective effects on neuronal apoptosis and supports functional recovery in a rat SCI model by activating the Wnt/β‐catenin signaling pathway. In specific, Simv administration after SCI significantly up‐regulated the expression of low density lipoprotein receptor‐related protein 6 phosphorylation and β‐catenin protein, increased the mRNA expression of lymphoid enhancer factor‐1 and T‐cell factor‐1, and suppressed the expression of β‐catenin phosphorylation in the spinal cord neurons. Simv enhanced motor neuronal survival in the spinal cord anterior horn and decreased the lesion of spinal cord tissues after SCI. Simv administration after SCI also evidently reduced the expression levels of Bax, active caspase‐3, and active caspase‐9 in the spinal cord neurons and the proportion of transferase UTP nick end labeling (TUNEL)‐positive neuron cells, but increased the expression level of Bcl‐2 in the spinal cord neurons. However, the anti‐apoptotic effects of Simv were reduced in cultured spinal cord nerve cells when the Wnt/β‐catenin signaling pathway was suppressed in the lipopolysaccharide‐induced model. Furthermore, the Basso, Beattie, and Bresnahan scores indicated that Simv treatment significantly improved the locomotor functions of rats after SCI. This study is the first to report that Simv exerts neuroprotective effects by reducing neuronal apoptosis, and promoting functional and pathological recovery after SCI by activating the Wnt/β‐catenin signaling pathway. We verified the neuroprotective properties associated with simvastatin following spinal cord injury (SCI). Simvastatin reduced neuronal apoptosis, improved the functional and pathological recovery via activating Wnt/β‐catenin signal pathway, however, the anti‐apoptosis effects of simvastatin were reversed following suppressing Wnt/β‐catenin signaling pathway in primary spinal cord neurons. The significant findings may provide clinical therapeutic value of simvastatin for treating SCI. Abstract : We verified the neuroprotective properties associated with simvastatin following spinal cord injury (SCI). Simvastatin reduced neuronal apoptosis, improved the functional and pathological recovery via activating Wnt/β‐catenin signal pathway, however, the anti‐apoptosis effects of simvastatin were reversed following suppressing Wnt/β‐catenin signaling pathway in primary spinal cord neurons. The significant findings may provide clinical therapeutic value of simvastatin for treating SCI.